Wordpress for web developers : an introduction for web professionals - Leary, Stephanie (Expert's voice in Web development., 2013)
WordPress for Web Developers is a complete guide for web designers and developers who want to begin building and administering sites with WordPress. This book is an update of Beginning WordPress 3, freshened and clarified for web developers who want to make the most of WordPress. You'll start by learning WordPress basics, including how to publish content, add media, and manage users. Then you'll dig deeper into your WordPress server administration, including domain mapping, security, and importing and migrating. The book then steps up a gear with an introduction to developing for WordPress, perfect for developers and designers with some PHP experience, who want to learn to create custom themes and plugins. WordPress is the most popular open source blogging and content management system in the world. Its flexible, user-friendly system can be extended with thousands of freely available themes and plugins. This book will teach you how to make the most of WordPress's built-in features, how to find the right themes and plugins for your projects, and how to build your own custom features. You'll learn to.